Cross-border shopping in the Euregio Rhine-Meuse-North - Arts, Carla (Cross-border business development in the Dutch-German borderland, 2021)
Keywords: Einkaufen; Euregio Rhein-Maas-Nord

Les pratiques du quotidien transfrontalières dans la Grande Région SaarLorLux - Wille, Christian (UniGR-CBS Working Paper, 2019)
Abstract: „This paper analyses everyday practices carried out by the residents of the Saarland, Lorraine, Luxembourg, Rhineland-Palatinate and Wallonia in the neighbouring regions abroad. The key assumption is the consideration that the inhabitants of the Greater Region SaarLorLux define the transborder reality of life of this region through their cross-border performance of everyday practices. Such a socio-constructivist perspective is not interested in what the Greater Region SaarLorLux actually is, but in what ways it is constituted or how it manifests itself in the daily lives of its inhabitants. Therefor the most common cross-border everyday practices, such as shopping for everyday needs, leisure-time shopping, outdoor recreation/tourism, cultural events, as well as visiting friends and family are looked at in greater detail. These observations are based on selected findings from three recent empirical studies of the study region, which have been linked to each other as well as socio-culturally and socioeconomically mapped in order to carve out the spatial organization, the motives and other contextual factors of cross-border everyday practices in the Greater Region SaarLorLux. This approach allows reconstructing mobility flows and spatial emphases in the context of everyday practices and gives insights into the nature of cross-border living realities in the Greater Region SaarLorLux.“
Keywords: Alltag; Einkaufen; Familie; Internationale Mobilität; Saar-Lor-Lux; Tourismus

Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch

Grenzüberschreitende Alltagspraktiken in der Großregion SaarLorLux. Eine Bestandsaufnahme - Wille, Christian (Lebenswirklichkeiten und politische Konstruktionen in Grenzregionen. Das Beispiel der Großregion SaaLorLux. Wirtschaft – Politik – Alltag – Kultur, 2015)
Abstract: „In diesem Beitrag werden Alltagspraktiken untersucht, die von den Einwohnern des Saarlandes, Lothringens, Luxemburgs, von Rheinland-Pfalz und Wallonien in angrenzenden Regionen im Ausland ausgeführt werden. Dafür leitend ist die Überlegung, dass sich die Großregion SaarLorLux anhand der grenzüberschreitenden Ausführungen von Alltagspraktiken ihrer Bewohner als grenzüberschreitende Lebenswirklichkeit bestimmen lässt. In einer solchen sozialkonstruktivistischen Perspektive wird nicht danach gefragt, was die Großregion SaarLorLux ist, sondern auf welche Weisen sie konstituiert wird bzw. wie sie sich im Alltag ihrer Bewohner manifestiert. Dafür werden die am häufigsten grenzüberschreitend ausgeführten Alltagspraktiken näher betrachtet, zu denen das Einkaufen für den täglichen Bedarf, das freizeitorientierte Shoppen, das Erholen im Grünen/Tourismus, das Besuchen von kulturellen Veranstaltungen sowie das Besuchen von Freunden und Familienmitgliedern zählen. Die Betrachtungen basieren auf drei rezenten empirischen Studien im Untersuchungsraum und daraus ausgewählten Befunden, die zueinander in Beziehung gesetzt sowie soziokulturell und sozioökonomisch eingeordnet werden mit dem Ziel, die räumliche Organisation, die Motive und andere Kontextfaktoren von grenzüberschreitenden Alltagspraktiken in der Großregion SaarLorLux herauszuarbeiten. Über dieses Vorgehen werden Mobilitätsströme und räumliche Schwerpunkte im Kontext von Alltagspraktiken rekonstruiert und Einblicke gegeben in die Beschaffenheit von grenzüberschreitenden Lebenswirklichkeiten in der Großregion SaarLorLux.“
Keywords: Alltag; Einkaufen; Familie; Tourismus

Cross-Border Differences and Unfamiliarity. Shopping Mobility in the Dutch-German Rhine-Waal Euroregion - Spierings, Bas; Velde, Martin van der (European Planning Studies, 2013)
Keywords: Einkaufen; Euregio Rhein-Waal; Grenzgebiet; Mobilität

Les pratiques commerciales dans une région frontalière. Les exemples d’Arlon, de Luxembourg-ville et de Metz - Smits, Florence (Belgeo, 2006)
Abstract: „Parts of Belgium, France, Germany and Luxembourg which comprise the Great Region have witnessed an increase in the mobility of workers and in the degree of political collaboration. Nevertheless, this evolution does not seem to have had an impact on the consumption habits of workers who tend to remain quite different in Arlon, Luxembourg and Metz. In contrast, people with less mobility but more time available, such as the retired and young, seem to exhibit the same pattern of consumption.“
Keywords: Arlon; Einkaufen; Grenzarbeitnehmer; Handel; Luxemburg (Stadt); Metz; Mobilität; Verbrauch

Einzugsgebiete ausgewählter Geschäftszentren in Grenznähe zwischen Nordhorn und Venlo - Meschede, Winfried (Westmünsterland - Ostniederlande. Entwicklung und Stellung eines Grenzraumes. Vorträge auf der Jahrestagung der Geographischen Kommission in Vreden 1983, 1984)
Keywords: Bocholt; Einkaufen; Einzelhandel; Emmerich am Rhein; Enschede; Grenzüberschreitende Regionalplanung; Gronau (Westf.); Kleve (Kreis Kleve); Münsterland (West); Niederlande (Ost); Nimwegen; Nordhorn; Venlo; Winterswijk